2021
DOI: 10.3390/jmse9070736
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Interaction between Submarine Landslides and a Monopile Using CFD Techniques

Abstract: Offshore installations with pile foundations in shallow water are vulnerable to submarine landslides, which cause serious damage to engineering facilities, loss of life, and loss of money. Due to a shortage of real observation data and the difficulty of reproduction, we lack insight into the interaction behavior between submarine landslides and monopiles. This study capitalized on ANSYS Fluent 20.0 to develop a three-dimensional biphasic (water and slurry) numerical model. This CFD model was used to analyze th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…According to field geological surveys, the densities (ρ L ) of seabed landslides are taken as 1400 kg/m 3 , 1600 kg/m 3 , and 1800 kg/m 3 , respectively [50]. The impact heights (h) of seabed landslides are taken as 5 m, 6 m, 7 m, 8 m, and 9 m, respectively [28].…”
Section: The Influence Of Different Types Of Submarine Landslides On ...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to field geological surveys, the densities (ρ L ) of seabed landslides are taken as 1400 kg/m 3 , 1600 kg/m 3 , and 1800 kg/m 3 , respectively [50]. The impact heights (h) of seabed landslides are taken as 5 m, 6 m, 7 m, 8 m, and 9 m, respectively [28].…”
Section: The Influence Of Different Types Of Submarine Landslides On ...mentioning
confidence: 99%
“…Li et al [27] conducted 12 experiments in a submarine landslide model trough and optimized the formula for a dimensionless resistance coefficient acting on pile foundations by adjusting variables such as the slope of the model trough and the mass fraction of kaolin clay in the landslide body. Li et al [28] employed computational fluid dynamics to study the impact force of submarine debris flows on the monopile and analyzed the characteristics of the drag force acting on the monopile. Li et al [16] simulated the impact of submarine debris flows on pile foundations using computational fluid dynamics and proposed a formula for predicting impact forces.…”
Section: Introductionmentioning
confidence: 99%
“…Rigorous analysis for 36 cases was performed to investigate the combined effect of the impact pressure, impact angle, and wall thickness, as revealed in Table 2. These three parameters are considered very influential for the strength of the pipeline during debris flow [33][34][35]. A different set of parameters were considered in the analysis to observe the critical condition of the pipeline when approaching failure in a broad spectrum, which is discussed in the subsequent sections.…”
Section: Finite Element Modellingmentioning
confidence: 99%
“…To simulate the interaction between submarine landslides and a monopile, a threedimensional water-slurry biphasic model was developed in [2]. The numerical results indicated that the debris flow height on the interaction force is significant at low-velocity stages, while the peak force representing a hazard level for the monopile is non-negligible under high-flow-velocity and low-flow-height conditions.…”
Section: (1) Pile or Monopile Foundationsmentioning
confidence: 99%